A Single-Center Multidisciplinary Initiative to Reduce Catheter-Associated Urinary Tract Infection Rates. Issue 3 (July 2015) - Sutherland, Tori; Beloff, Jennifer; McGrath, Casey; Liu, Xiaoxia; Pimentel, Marc T.; Kachalia, Allen; Bates, David; Urman, Richard D.
<x xml:space="preserve">Abstract</x> Catheter-associated urinary tract infection (CAUTI) is an important patient safety issue that is responsible for an estimated 449334 annual infections, with an average direct cost of 790-1200 per infection. In total, the cost associated with CAUTI is estimated to be 115 million to 1.82 billion annually. We conducted an internal revenue analysis with a standard sensitivity analysis to assess the impact of a low-cost CAUTI reduction program on direct costs to the hospital over four years. The interventions included the formation of a multidisciplinary CAUTI reduction task force, formal data collection in all ICUs, staff education, and new electronic order sets with decision support. During the initial intervention period, the infection rate per 1000 catheter days decreased from 5.4 to 1.5. In the second year of the program, the infection rate increased to 4.6. After additional interventions were launched, infection rates decreased to 2.2. Cost savings per 1000 catheter days (±20%) during the initial intervention were 4501 (3600-5401). Our intervention demonstrated that provider education and electronic documentation prompts were followed by a significant decrease in catheter utilization, that in turn was followed by lower infection rates. Decreased emphasis on intervention goals were followed by an increase in CAUTI rates. Our subsequent interventions suggest that upward trends may be reversible.